Transglycosylation Properties of a Novel α-1,4-Glucanotransferase from Bacteroides thetaiotaomicron and Its Application in Developing an α-Glucosidase-Specific Inhibitor - Hye-Jeong Choi; Dam-Seul Ko; Na-Ri Kim; Woo-Jae Choung; Ye-Seul Koo; Da-Woon Jeong; Jae-Hoon Shim (Journal of Chemistry)
In this study, α-glucanotransferase from Bacteroides thetaiotaomicron was expressed in Escherichia coli and characterized. Conserved amino-acid sequence alignment showed that Bacteroides thetaiotaomicron α-glucanotransferase (BtαGTase) belongs to the glycoside hydrolase family 77. The enzyme exhibited optimal catalytic activity at 60°C and pH 3.0. BtαGTase catalyzed transglycosylation reactions that produced only glycosyl or maltosyl transfer products, which are preferable for the generation of transglycosylated products with high yield. The 1-deoxynojirimycin (DNJ) glycosylation product G1-DNJ was generated using BtαGTase, and the inhibitory effect of G1-DNJ was analyzed. A kinetic study of inhibition revealed that G1-DNJ inhibited α-glucosidase to a greater extent than did DNJ but did not show any inhibitory effects towards α-amylase, suggesting that G1-DNJ is a potential candidate for the prevention of diabetes.